THE IMPROVING SPEAKING SKILLS THROUGH DIALOG METHOD IN MA NURULHUDA SUMENEP ACADEMIC YEAR 2019- 2020 - Sulis Triana Dewi; Yuliarsih Yuliarsih (The Ellite of Unira, 2021)
The research are formuated to find out there is any correlation between students’ intrinsic motivation and reading comprehension in seventh grade smp al-maarif panggung. This analysis used two variable. Students’ intrinsic motivation as independent variable and reading comprehension as dependent variable.The method used in this research was a correlation method. The population of this research is seventh grade smp al-maarif panggung by systematic sampling techniques, the research takes consist of 23 students. The instrument collecting data are questionnaire and test. The questionnaire was used to get the data of students’ intrinsic motivation and test for reading comprehension. To validity test of instruments this research used content validity and to the reliability test of instrument used two method. Alpha cronbach to test the reliability of questionnaire and guttman split-half to test reliabilty of test. In the analyzing the data, the researcher used Pearson Product Moment by SPSS v.26 program. The result of this research showed that there is correlation between students’ intrinsic motivation and reading comprehension with the r value is (0,787) > rt (0.413) it means that the students’ intrinsic motivation and reading comprehension coefficient correlation and the category is strong correlation.